Alternate cropping systems for food and nutritional security in eastern India - Kumar, Rakesh; Krishna, Bal; Kumar, Sanjeev (Indian Farming, 2023)
There is an urgent need for identification of the eco-friendly/cleaner production system that is more productive and profitable, efficient user of energy, water and carbon-based inputs, and environmentally safer. In India, there are more than 80 pre-dominant cropping production systems. Continuous growing of the existing pre-dominant cropping system has resulted in stagnation or decline in crop productivity, particularly in rice-wheat system in the Indo-Gangetic Plains. Excess use of inorganic fertilizers along with frequent use of pesticides and climate change have adversely impacted the soil health, productivity and thereby livelihood and nutritional security of small and marginal farmers. Hence, there is a need to develop the site specific an alternate cropping system for efficient utilization of available resources and to maintain stability in agricultural production systems for a longer period, and get a higher profit. This will support for the crop modeling, policymakers, government planners, researchers and producers to achieve the sustainable development goals in Indo-Gangetic Plains and similar agro-climatic conditions of south Asia.